Acidophilous oak forests of the Wielkopolska region (West Poland) against the background of Central Europe - Kasprowicz, Marek (Biodiversity: Research and Conservation, 2011)
This monograph gives the phytosociological characteristics of acidophilous oak forests from the class Quercetea robori-petraeae (Aulacomnio androgyni-Quercetum, Molinio caeruleae-Quercetum, and Calamagrostio arundinaceae-Quercetum) and the closely related forest communities from the classes Querco-Fagetea (Potentillo albae-Quercetum and acidophilous forms of Galio sylvatici-Carpinetum) and Vaccinio-Piceetea (Querco roboris-Pinetum and Serratulo-Pinetum) in the Wielkopolska region and adjacent areas. The report is based on 1655 relevés selected from 59 published or unpublished studies. The analysed and revised syntaxa are described in accordance with the International Code of Phytosociological Nomenclature. The distribution of the documented localities of all associations and subassociations in the study area is shown in cartograms on the ATPOL grid (squares of 10 km x 10 km). The classical phytosociological methods are complemented with multivariate ordination methods (detrended correspondence analysis and/or principal component analysis) and analyses taking into account Ellenberg indicator values. The natural geographical and site differentiation of all the plant associations is presented, and stages of degeneration are distinguished in some of them. The separation of degenerated forms and substitute forest communities has allowed a clearer classification of the studied syntaxa. This study shows that the analysed associations can be subdivided into 16 subassociations and 23 variants. For 5 subassociations, nomenclatural types are designated here. The most common association in the study area is Calamagrostio arundinaceae-Quercetum, but most of its relevés represent various stages of degeneration. Among communities from the order Quercetalia roboris, patches of Aulacomnio androgyni-Quercetum and Molinio caeruleae-Quercetum are rare. On the basis of this detailed study, a coherent system of classification of acidophilous oak forests from the order Quercetalia roboris in Central Europe is proposed. The results are important for biodiversity conservation and sustainable forest management.